A child had to calculate ( 3 n + k − 1 ) but instead he calculated ( 4 n + k ) . Interestingly both the answers were same. What is the maximum possible value of ( k n + 4 ) × ( k + 1 k + 3 ) . You may use a calculator for a final step. Given n and k are whole numbers.
This problem is a part of the series <One minute problems>
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The topic should be ''Discrete mathematics''.
From "n choose r" ( click here for background info ), we can rewrite the first two statements like so:
6 × ( n + k − 4 ) ! ( n + k − 1 ) ! = 2 4 × ( n + k − 4 ) ! ( n + k ) !
Multiplying both sides by 2 4 × ( n + k − 4 ) ! gives us:
4 × ( n + k − 1 ) ! = ( n + k ) !
From this we can conclude that n + k = 4 , since it is the multiplier between two consecutive factorials. We the know that n = 4 − k , allowing us to write the question in terms of k :
( k 8 − k ) × ( k + 1 k + 3 )
As we know that n and k are whole numbers, n + k = 4 , and you can't have the factorial of negative integers, k = 0 , 1 , 2 , 3 , 4
k | 0 | 1 | 2 | 3 | 4 |
Result | 3 | 42 | 150 | 150 | 21 |
Hence the answer is 1 5 0
( 3 n + k − 1 ) = ( 4 n + k ) ⇒ 3 ! ( n + k − 4 ) ! ( n + k − 1 ) ! = 4 ! ( n + k − 4 ) ! ( n + k ) ! ⇒ n + k = 4 ∴ n = 4 − k
N o w ( k n + 4 ) × ( k + 1 k + 3 ) = ( k 8 − k ) × ( k + 1 k + 3 ) = k ! × ( 8 − 2 k ) ! ( 8 − k ) ! × ( k + 1 ) ! × ( k + 3 − k − 1 ) ! ( k + 3 ) ! = k ! × ( 8 − 2 k ) ! × 2 ( 8 − k ) ! × ( k + 3 ) × ( k + 2 )
Here k must be integer and it's limit is 0 ≤ k ≤ 4 . So, k = 0 , 1 , 2 , 3 , 4
By inputting k 's value in ( k n + 4 ) × ( k + 1 k + 3 ) = ( k 8 − k ) × ( k + 1 k + 3 ) ,
we find for k = 2 , 3 ; ( k 8 − k ) × ( k + 1 k + 3 ) = 1 5 0
and it is the largest.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Definition of Binomial Coefficient
( 3 n + k − 1 ) 3 ! ( n + k − 4 ) ! ( n + k − 1 ) ! 3 ! ( n + k − 4 ) ! ( n + k − 1 ) ! ⟹ n + k = ( 4 n + k ) = 4 ! ( n + k − 4 ) ! ( n + k ) ! = 4 ( 3 ! ) ( n + k − 4 ) ! ( n + k ) ( n + k − 1 ) ! = 4 Equating the two binomial coefficients Note that ( N M ) = N ! ( M − N ) ! M !
Now, let P ( k ) = ( k n + 4 ) ( k + 1 k + 3 ) = ( k 8 − k ) × 2 ! ( k + 1 ) ! ( k + 3 ) ! = ( k 8 − k ) × 2 ( k + 3 ) ( k + 2 ) . Since n + k = 4 , k can only take the value from 0 to 4.
P ( 0 ) P ( 1 ) P ( 2 ) P ( 3 ) P ( 4 ) = ( 0 8 ) × 2 3 × 2 = 1 × 3 = 3 = ( 1 7 ) × 2 4 × 3 = 7 × 6 = 4 2 = ( 2 6 ) × 2 5 × 4 = 1 5 × 1 0 = 1 5 0 = ( 3 5 ) × 2 6 × 5 = 1 0 × 1 5 = 1 5 0 = ( 4 4 ) × 2 7 × 6 = 1 × 2 1 = 2 1
The maximum P ( k ) = P ( 2 ) = P ( 3 ) = 1 5 0